Tourism and Peace in Economic Development Perspective of India - Mishra, P. K.; Verma, J. K. (Journal of Environmental Management and Tourism, 2017)
The importance of tourism as an instrument for revenue generation, employment creation and fostering economic growth is well established across the globe. Globally, tourism has been recognised as the largest service sector in terms of revenue generation and foreign exchange earnings. The sector also plays a crucial role in attaining the macroeconomic goal of growth with equity. Thus, tourism has been considered and observed to contribute to world peace. But this peace contribution depends on social and politic stability which in turn depends on the economic development of a nation. So, in this paper an effort has been made to assess the role of tourism in India as an engine of peace oriented sustainable economic development. It is found that tourism has the potential to positively influence the sustainable development of the country. Therefore, it is imperative to chalk out appropriate plans and policies for promoting tourism as a means of achieving sustainable development and unending peace.